2021
DOI: 10.1136/bmjopen-2021-053487
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prescribing pattern of opioid and benzodiazepine substitutes among Medicare part D beneficiaries from 2013 to 2018: a retrospective study

Abstract: ObjectiveOpioid and benzodiazepine co-prescribing is associated with a substantial increase in opioid overdose deaths. In this study, we examine the prescribing trends of substitutes of opioids and benzodiazepines alone or in combination, compared with opioids and benzodiazepines.DesignRetrospective cohort study.SettingData were collected using a 20% national sample of Medicare beneficiaries from 2013 to 2018.Participants4.1–4.3 million enrollees each year from 2013 to 2018.InterventionNone.Primary outcomeWe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…15,16 Gorfinkel et al 17 reported that following CDC recommendations in 2016, there was a decrease in prescription of opioids and an increase in prescription of nonopioids, including gabapentinoids (GABA) and antidepressants. Esechie et al 18 reported a similar pattern among Medicare beneficiaries. Drug Enforcement Agency and state lawmakers in the United States have also implemented policies limiting the use of opioids.…”
Section: Introductionmentioning
confidence: 76%
“…15,16 Gorfinkel et al 17 reported that following CDC recommendations in 2016, there was a decrease in prescription of opioids and an increase in prescription of nonopioids, including gabapentinoids (GABA) and antidepressants. Esechie et al 18 reported a similar pattern among Medicare beneficiaries. Drug Enforcement Agency and state lawmakers in the United States have also implemented policies limiting the use of opioids.…”
Section: Introductionmentioning
confidence: 76%
“…Pharmacologic opioid substitutes were not within the scope of this study because prior research identified trends in the use of gabapentinoids, selective serotonin reuptake inhibitors, and serotonin-norepinephrine reuptake inhibitors for pain treatment. 51 Use of gabapentinoids increased in prevalence over the study period but remained uncommon (<10%). Therefore, it is less likely that these medications were associated with the increases in nonpharmacologic treatments between 2016 and 2019.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to 2013 to 2018 trends among Medicare enrollees, we found increasing trends in the use of opioid substitutes, such as gabapentinoids, between 2011 and 2019. 51 This transition coincides with a growing awareness of an increased risk for falls and other complications when central nervous system-acting medications are concomitantly prescribed. 10 In addition, a limited referral network may explain the limited use of nonpharmacologic treatments.…”
Section: Discussionmentioning
confidence: 96%
“…A study of Part D prescriptions in 2018 showed that 30.4% of Medicare beneficiaries still received an opioid prescription that year. 29 While evidence for effective nonpharmacologic therapies are emerging, (e.g., cognitive behavioral therapy and exercise), few studies include in older adults with complex medical needs. 30 In our previous work, 31 we found that many older adults lack access to effective nonpharmacologic treatments and received receive little guidance from their primary care providers regarding effective pain interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an array of adverse effects associated with the use of opioids in older adults, 28 many clinicians still resort to their use given few accessible alternative strategies. A study of Part D prescriptions in 2018 showed that 30.4% of Medicare beneficiaries still received an opioid prescription that year 29 . While evidence for effective nonpharmacologic therapies are emerging, (e.g., cognitive behavioral therapy and exercise), few studies include in older adults with complex medical needs 30 .…”
Section: Discussionmentioning
confidence: 99%